A quantitative analysis of stem cell homeostasis in the Arabidopsis columella root cap - Hong, Jing Han; Chu, Huangwei; Zhang, Chen; Ghosh, Dipanjana; Gong, Ximing; Xu, Jian (Frontiers in Plant Science, 2015)
The Lugol’s staining method has been widely used to detect changes in the maintenance of stem cell fate in the columella root cap of Arabidopsis roots since the late ‘90s. However, various limitations of this method demand for additional or complementary new approaches. For instance, it is unable to reveal the division rate of columella root cap stem cells. Here we report that, by labelling dividing stem cells with 5-ethynyl-2´-deoxyuridine (EdU), the number and distribution of their labeled progeny can be studied so that the division rate of stem cells can be measured quantitatively and in addition, that the progression of stem cell progeny differentiation can be assessed in combination with Lugol’s staining. EdU staining takes few hours and visualization of the stain characteristics of columella root cap can be performed easily under confocal microscopes. This simple technology, when used together with Lugol’s staining, provides a novel quantitative method to study the dynamics of stem cell behaviour that govern homeostasis in the Arabidopsis columella root cap.